2011
DOI: 10.1177/1947603510392023
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Cartilage Repair with Bone Marrow Aspirate Concentrated Cells and Collagen Matrix in Full-Thickness Knee Cartilage Lesions

Abstract: Objective:The purpose of our study was to determine the effectiveness of cartilage repair utilizing 1-step surgery with bone marrow aspirate concentrate (BMAC) and a collagen I/III matrix (Chondro-Gide, Geistlich, Wolhusen, Switzerland).Materials and Methods:We prospectively followed up for 2 years 15 patients (mean age, 48 years) who were operated for grade IV cartilage lesions of the knee. Six of the patients had multiple chondral lesions; the average size of the lesions was 9.2 cm2. All patients underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
170
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(191 citation statements)
references
References 49 publications
14
170
0
7
Order By: Relevance
“…Sto sun ko wo nie daw no roz po czę to sto so wa nie jed no eta po wych pro ce dur ope ra cyj nych, gdzie ho dowa ne chon dro cy ty za stą pio no me zen chy mal ny mi ko mór ka mi ma cie rzy sty mi po zy ski wa ny mi naj czę -ściej z krwi, szpi ku lub tkan ki tłusz czo wej [7,8,9,10,11,12].…”
Section: Wstępunclassified
See 2 more Smart Citations
“…Sto sun ko wo nie daw no roz po czę to sto so wa nie jed no eta po wych pro ce dur ope ra cyj nych, gdzie ho dowa ne chon dro cy ty za stą pio no me zen chy mal ny mi ko mór ka mi ma cie rzy sty mi po zy ski wa ny mi naj czę -ściej z krwi, szpi ku lub tkan ki tłusz czo wej [7,8,9,10,11,12].…”
Section: Wstępunclassified
“…Po po bra niu chon dro cy tów ist nie je ko niecz ność ich na mno że nia w la bo ra to rium i na stęp nie ich wszcze pie nia. Z uwa gi na ho dow lę w wa run kach la bo ra toryj nych, jak i 2 se an se ope ra cyj ne, pro ce du ra ta jest wy so ce kosz tow na i bar dziej kło po tli wa dla pa cjen ta.Sto sun ko wo nie daw no roz po czę to sto so wa nie jed no eta po wych pro ce dur ope ra cyj nych, gdzie ho dowa ne chon dro cy ty za stą pio no me zen chy mal ny mi ko mór ka mi ma cie rzy sty mi po zy ski wa ny mi naj czę -ściej z krwi, szpi ku lub tkan ki tłusz czo wej [7,8,9,10,11,12].W na szym ośrod ku do re kon struk cji głę bo kich ubyt ków chrzęst no -kost nych sto so wa no kon cen trat ko mó rek szpi ku kost ne go oraz me zen chy mal ne komór ki ma cie rzy ste po zy ska ne z krwi ob wo do wej.Wstęp ne wy ni ki le cze nia cho rych by ły sa tys fakcjo nu ją ce w oce nie ope ra to rów i in spi ro wa ły do dalszych ob ser wa cji, Ce lem pra cy by ła oce na od le głych wy ni ków kli nicz nych po re kon struk cji roz le głych ubyt ków chrzęst no -kost nych w dwóch gru pach cho rych za opatrzo nych z uży ciem me zen chy mal nych ko mó rek macie rzy stych z krwi lub kon cen tra tu ko mó rek szpi ku. …”
unclassified
See 1 more Smart Citation
“…Along these lines, Gobbi et al (56) published the first case of stem cell transplantation using the onestep procedure to operate on a knee, with two years of follow-up. The procedure consisted of using bone marrow cells together with scaffolds of types I and III collagen.…”
Section: One-step Stem Cell Transplantationmentioning
confidence: 99%
“…[86][87][88] Several studies have reported BMC to be effective in treatment of early knee OA and moderate focal chondral defects.…”
mentioning
confidence: 99%